PENGEMBANGAN MODUL BERBASIS PROBLEM BASED LEARNING UNTUK MATERI USAHA DAN ENERGI DI SMA (SESUAI KURIKULUM 2013) - Mohamad Ardian Leonda; Desnita Desnita; Agus Setyo Budi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research aims to develop a module with a step by step problem based learning, which measures the activity is designed primarily to help learners develop their thinking, problem solving, and intellectual skills, which with their experience through real or simulated situations and become students independent. This study research approach development (development research) with stage 1) assess the demands of curriculum standards and teacher inventory problems; 2) the design of the module, module manufacturing and test validation by experts; 3) the stage of implementation, the module tested against high school students of class XI to know the students' assessment module. Based on the results obtained it can be concluded that the media were developed suitable to be used as learning materials physics.Keywords: development research, module, problem based learning.